Reducing process cost and CO2 emissions for extractive distillation by double-effect heat integration and mechanical heat pump. (15th March 2016) - You, Xinqiang; Rodriguez-Donis, Ivonne; Gerbaud, Vincent
Highlights: We study heat integration and mechanical heat pump processes for the extractive distillation. We propose a new objective function for optimizing heat integrated extractive distillation processes. We propose a novel partial heat integration process and two partial mechanical heat pump processes. The proposed optimal partial HI process gives the lowest TAC and the full BF process produces the lowest CO2 emissions. The novel mechanical heat pump processes can effectively reduce initial investments and total annual cost. Abstract: Double-effect heat integration and mechanical heat pump technique are investigated for the extractive distillation process of the acetone–methanol minimum boiling azeotropic mixture with entrainer water and compared from the economical view by the total annual cost (TAC) and environmental aspect by CO2 emissions. Firstly, A novel optimal partial heat integration (OPHI) process is proposed and optimized through the minimization of a newly defined objective function called OF2 that describes the energy consumption used per product unit flow rate and allows comparison with the literature direct partial and full heat integration processes. We find that the minimum TAC is not achieved by the full heat integration process as intuition, but by the new OPHI process. Secondly, the vapour recompression (VRC) and bottom flash (BF) mechanical heat pump processes are evaluated with respect to energy and CO2 emissions. We proposed a new partial VRC and a new partial BF process in order to reduce the high initial capital cost of compressors. Overall the results show that compared to the conventional extractive distillation process the proposed OPHI process gives a 32.2% reduction in energy cost and a 24.4% saving in TAC while the full BF process has the best performance in environmental aspect (CO2 emissions reduce by 7.3 times).